Article Review : Peran Hipertensi terhadap Patomekanisme Stroke Iskemik dan Hemoragik - Muhammad Arbyanka Diontama; TA Larasati; Anisa Nuraisa Jausal (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Stroke is a syndrome characterized by sudden focal neurological deficits caused by vascular injury, either hemorrhage or infarction in the central nervous system. According to the World Health Organization, approximately 15 million people experience stroke worldwide each year, with 5 million resulting in death and another 5 million suffering permanent disability. Hypertension is a major risk factor for both ischemic and hemorrhagic stroke, mediated by complex pathophysiological mechanisms. This review aims to explore the mechanisms by which hypertension contributes to the pathophysiology of stroke based on current evidence. The study adopts a literature review approach, utilizing data sources from journal articles, books, and other relevant documents accessible online via search engines such as Google Scholar®, PubMed®, and ScienceDirect®. The findings indicate that ischemic stroke occurs due to atherosclerosis and microvascular dysfunction induced by hypertension, whereas hemorrhagic stroke involves vessel rupture resulting from arterial wall weakening. Hypertension also affects the permeability of the blood-brain barrier through molecular pathways such as vascular endothelial growth factor (VEGF) release, leading to cerebral edema. Studies demonstrate that effective blood pressure control can significantly reduce the risk of stroke by up to 41%, underscoring hypertension as a primary target in stroke prevention.